2021
DOI: 10.1111/febs.16261
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition alters mitotic progression through the upregulation of centromeric α‐Satellite RNAs

Abstract: Cell cycle progression requires control of the abundance of several proteins and RNAs over space and time to properly transit from one phase to the next and to ensure faithful genomic inheritance in daughter cells. The proteasome, the main protein degradation system of the cell, facilitates the establishment of a proteome specific to each phase of the cell cycle. Its activity also strongly influences transcription. Here, we detected the upregulation of repetitive RNAs upon proteasome inhibition in human cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Satellite DNA repeats located in (peri)centromeric heterochromatin are actively transcribed with transcripts being necessary for the formation and maintenance of heterochromatin as well as centromere function [ 12 , 13 , 14 ]. The presence of transcription factor binding sites was predicted and experimentally proven for different satellite DNAs [ 15 , 16 ] and transcription, which is often bidirectional, proceeds from internal promoters, usually by RNA polymerase II (RNA Pol II; [ 17 , 18 , 19 , 20 , 21 ]). Under physiological conditions, satellite DNA expression is low, and it is temporally and spatially regulated [ 18 , 22 , 23 ].…”
Section: Regulation Of Satellite Dna Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite DNA repeats located in (peri)centromeric heterochromatin are actively transcribed with transcripts being necessary for the formation and maintenance of heterochromatin as well as centromere function [ 12 , 13 , 14 ]. The presence of transcription factor binding sites was predicted and experimentally proven for different satellite DNAs [ 15 , 16 ] and transcription, which is often bidirectional, proceeds from internal promoters, usually by RNA polymerase II (RNA Pol II; [ 17 , 18 , 19 , 20 , 21 ]). Under physiological conditions, satellite DNA expression is low, and it is temporally and spatially regulated [ 18 , 22 , 23 ].…”
Section: Regulation Of Satellite Dna Expressionmentioning
confidence: 99%
“…Namely, CENP-B promotes the binding of the zinc-finger transcriptional regulator (ZFAT) which activates RNA Pol II transcription through histone modification H4K8Ac. α satellite RNA level fluctuates throughout the cell cycle, peaking in the G2/M phase [ 21 ], being controlled by the proteasome [ 16 ]. Satellite RNA interacts with members of the cohesin ring, suggesting a role for these transcripts in the regulation of mitotic progression [ 16 ].…”
Section: Regulation Of Satellite Dna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the centromere and the pericentromere bear epigenetic repressive marks, they can also display histone post-translational modifications associated with active chromatin. Basal centromeric expression is detectable in normal human cells from different tissues ( Eymery et al, 2009 ), even by Northern blot ( Caceres-Gutierrez et al, 2022 ). But these regions are also transcriptionally dynamic and highly responsive to the cellular context and internal and external stimuli, such as cell cycle progression ( Bury et al, 2020 ), differentiation ( Bouzinba-Segard et al, 2006 ), cancer progression ( Ting et al, 2011 ; Zhu et al, 2011 ), heat shock, osmotic pressure, oxidative stress, and exposure to heavy metals ( Valgardsdottir et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have demonstrated that proteasome inhibitors promote the overexpression of several repetitive RNAs, including the centromeric α-satellites ( Caceres-Gutierrez et al, 2022 ). Centromeric and pericentromeric lncRNAs have also been associated with resistance to different antineoplastic drugs, such as the proteasome inhibitor bortezomib ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%